Determination of in situ ruminal degradation of phytate phosphorus from single and compound feeds in dairy cows using chemical analysis and near-infrared spectroscopy. (5th July 2020) - Haese, E.; Krieg, J.; Grubješić, G.; Feyder, A.; Rodehutscord, M.
Abstract : The ruminal degradation of P bound in phytate (InsP 6 ) can vary between feeds, but data on ruminal degradation of InsP6 from different feedstuffs for cattle are rare. One objective of this study was to increase the data base on ruminal effective degradation of InsP6 (InsP 6 ED ) and to assess if InsP6 ED of compound feeds (CF ) can be calculated from comprising single feeds. As a second objective, use of near-infrared spectroscopy (NIRS ) to predict InsP6 concentrations was tested. Nine single feeds (maize, wheat, barley, faba beans, soybeans, soybean meal (SBM ), rapeseed meal (RSM ), sunflower meal (SFM ), dried distillers' grains with solubles (DDGS )) and two CF (CF1 /CF2 ), consisting of different amounts of the examined single feeds, were incubated for 2, 4, 8, 16, 24, 48 and 72 h in the rumen of three ruminally fistulated Jersey cows. Samples of CF were examined before (CF1 /CF2 Mash ) and after pelleting (CF1/CF2 Pellet ), and InsP6 ED was calculated for all feeds at two passage rates (InsP 6 ED 5 : k = 5%/h; InsP 6 ED 8 : k = 8%/h). For CF1 and CF2, InsP6 ED was also calculated from values of the respective single feeds. Near-infrared spectra were recorded in duplicate and used to establish calibrations to predict InsP6 concentration. Besides a global calibration, also local calibrations were evaluated by separating samples into different data sets based on their origin. The InsP6 ED8 was highest for faba beans (91%), followed by maize (90%), DDGS (89%), soybeans (85%), wheat (76%) and barley (74%). Lower values were determined for oilseed meals (48% RSM, 65% SFM, 66% SBM). Calculating InsP6 ED of CF from values of single feeds underestimated observed values up to 11 percentage points. The NIRS calibrations in general showed a good performance, but statistical key data suggest that local calibrations should be established. The wide variation of InsP6 ED between feeds indicates that the ruminal availability of P bound in InsP6 should be evaluated individually for feeds. This requires further in situ studies with high amounts of samples for InsP6 analysis. Near-infrared spectroscopy has the potential to simplify the analytical step of InsP6 in the future, but the calibrations need to be expanded.